Sucrose, Reducing Sugars,and Carotenoid Content of Aceh Besar Sweet Potato Cultivars (Ipomoea batatas L) - Zaidiyah Zaidiyah (Jurnal Teknologi dan Industri Pertanian Indonesia, 2014)
Sweet potato is considered as an important food crop and it is known as one of the most productive carbohydrate-producing crop. This crop requires less inputs and water in comparison to rice, corn, or potato. Its wide adaptation to various agro ecological conditions has made sweet potato as a promising crop for saving life particularly during food (rice) shortage. The crop contained higher vitamin (A) and minerals that could help women and children aged below five preventing certain diseases. However, the nutritional value of sweet potato is various from one cultivar to another. It was assumed that geographical and environmental factors would influence the nutritional value of the tubers. Therefore, the following study was investigating the nutritional value of local cultivars in Aceh Besar District. Total carotenoid content of sweet potato varied from 1.86to 3.06 mg 100g-1 DM. The highest carotenoid was recorded by cv. Keupila  from Saree Sub-district.